Empowering Employees through BYOD: Benefits and Challenges in Malaysian Public Sector - Mahat, Norhazilah binti; binti Ali, Nor’ashikin (International Journal of Engineering and Technology, 2018)
In today's world, the development of new technologies has transformed the way employees perform their tasks without the limit of time and place. Bring Your Own Device (BYOD) is a concept to enable employees to perform their tasks with the limitless infrastructure, which allows mobility and access to anyone, anywhere using their own devices. The growing trends of BYOD have many benefits including increased employeesâ€™ productivity, increased employee satisfaction, and reduced costs. Â Despite the benefits, companies are also facing challenges such as security, loss and stolen of device and data, as well as malware attacks. One of the reasons for these challenges is that the BYOD policy is still not established and enforced in the public sector. Failure to create BYOD policy will have a negative impact on the organisation. However, issues and benefits are only anecdotes and they are not empirically studied in the public sector.Â Therefore, this study aims to identify benefits and challenges in Malaysian Public Sectors (MPS). Through literature review, benefits and challenges were extracted to list out the construct by measuring the frequency of constructs appearing in the literature. For that purpose, the quantitative survey will be conducted.